KEHADIRAN NEGARA MELALUI KEBIJAKAN OTONOMI KHUSUS DI PAPUA (Studi Kasus Dampak Otsus Pada Ekonomi Orang Asli Papua) - KAMBU, YOSEP (JURNAL BADATI, 2020)
The enactment of Special Autonomy from the Central Government to the RegionalGovernment of Papua is clear evidence of the presence of the state among indigenousPapuans to encourage development in the regions in the social economy. However,problems arise in the management of the special autonomy funds that are not yet optimal,the existence of corruption, collusion and nepotism, irregularities in regulations, andinadequate services. This article examines the impact of the presence of the state throughspecial autonomy among indigenous Papuans in the economic field. The approach usedin this research is qualitative using the case study method. Data collection techniques inthe form of interviews, observation, and documentation study. The study found that thegovernance of the Special Autonomy Fund has not been on target, indigenous Papuansare still at the poverty line, empowerment and community assistance programs have notbeen optimal, practices of corruption, collusion and nepotism occur, social disparitiesoccur, and abuse of special autonomy regulations. Thus, the presence of the state inPapua through the special autonomy policy must be re-evaluated. The state must ensurethat at the end of the special autonomy era, there should not be any indigenous Papuanswho are only spectators so that the aspirations for the welfare of all indigenous Papuansthrough special autonomy can be realized.